Street dreams - Kellerman, Faye. (New York : Warner Books, 2003)
Rescuing a newborn that has been abandoned in a dumpster, LAPD officer Cindy Decker, the wife of detective Peter Decker, begins a quest through inner-city Hollywood in search of the baby's mother and uncovers a dangerous drug ring.
Keywords: Decker, Peter (Fictitious character) -- Fiction; Lazarus, Rina (Fictitious character) -- Fiction; Police -- California -- Los Angeles -- Fiction; Abandoned children -- Fiction; Police spouses -- Fiction; Policewomen -- Fiction; Los Angeles (Calif.) -- Fiction; Mystery fiction